The republic unsettled : Muslim French and the contradictions of secularism - Fernando, Mayanthi L., 1975- (Duke University Press, 2014)
In 1989, three Muslim schoolgirls from a Paris suburb refused to remove their Islamic headscarves in class. The headscarf crisis signaled an Islamic revival among the children of North African immigrants; it also ignited an ongoing debate about the place of Muslims within the secular nation-state. Based on ten years of ethnographic research, The Republic Unsettled alternates between an analysis of Muslim French religiosity and the contradictions of French secularism brought to light by this Muslim identity.